Impact of Online Learning of Economics in Lebanon on Acquiring Essential Skills in Light of the COVID-19 Pandemic - El-Mousawi, Hasan; Zaraket, Mohamad; Bou-Assi, Claude (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
The sudden and recent outbreak of the Covid-19 had its impact on the way of life around the entire world; it challenged the education systems around the globe and forced schools and universities to switch to online education overnight. Several schools and universities that were formerly hesitant to change their traditional pedagogical approach had no choice but to entirely switch to online education. This study examines the impact of online learning of Economics on acquiring essential skills in light of the Coronavirus outbreak. The researchers used a descriptive-analytical approach and constructed a five-point Likert style questionnaire as a study tool. The questionnaire was distributed to a sample chosen from the population of Economics teachers in Lebanese schools. The sample consisted of 153 teachers all of which responded and their responses were valid for testing and analysis. The study reached some important findings mainly that through online learning of Economics, learners are not acquiring all of the 21st-Century skills, and the researchers had some recommendations as a result.